101 great answers to the toughest interview questions - Fry, Ron (Career P. Franklin LakesUS, 1996)
Seeks to give a preview to questions which interviewers ask, and suggests answers which can help interviewees to prepare themselves. Questions include: Have you ever been fired ? If you are happy at your current firm, why are you looking for another job ? and, How do you handle change ?